Manual de salud ocupacional para prevenir los accidentes de trabajo y las enfermedades profesionales del personal de la Empresa Megamodelauto cía. Ltda. en el cantón Santo Domingo de los Colorados, provincia de los Tsáchilas, año 2014 - Guajala Otavalo, Vicente Daniel (2015)
This research was conducted in Ecuador, specifically in the Tsáchila province in which has made the design of a manual of occupational health to prevent occupational accidents, which generate information and preventive measures so that the activities are developed effectively minimizing the incidence of accidents in the future. Supported in the use of scientific methods, which were giving guidelines for the development of procedures and support were in the process of analysis and interpretation of information supplied by primary sources can therefore build research findings . Through interviews with the directors of the company it was determined that most companies have ignorance of the rules, as it relates to issues of occupational safety and health the same as that granted to know the real situation on the misuse of safety equipment. This research aims to present a contribution in order to develop his collaborators certain behaviors, encouraging group participation of its members as human talent and thus managers will expose the real situation on safety at work, to have sign foundations in making correct and timely decisions essential offering an effective, efficient and quality service to all users of the company. A personnel meeting be informed, trained and comply with the appropriate regulations to carry out the work with the right team, are the fundamental pillars on which successful organizations sustain their achievements and to achieve this a manual of occupational health was developed so that minimum conditions relating to accidents at work and occupational diseases occur staff.